2015
DOI: 10.1177/1045389x15580659
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nano-silica and nano-magnetite on the magnetorheological fluid stabilization and magnetorheological effect

Abstract: In this study, the effect of adding magnetizable and non-magnetizable nano particles (magnetite and fumed silica) to magnetorheological fluids was investigated experimentally. The results showed a great increase up to six times in magnetorheological effect when using magnetite in comparison to nano particle–free magnetorheological fluids. On the other hand, adding non-magnetizable silica made the suspension stable for more than 2000 h by somehow increasing magnetorheological effect. Herschel–Bulkley model fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…big or small, spherical or not spherical, magnetically soft or hard, magnetic or non-magnetic, mechanically hard or soft, etc.). By using bidisperse MRFs one can improve dispersion stability, 95 reduce the off-state viscosity, 96 increase the MR effect 95,[97][98][99][100][101] and minimize the sedimentation. 97,98 First papers in this field explored mixing particles of different sizes (bimodal MRFs) with at least one particle in the micrometer range.…”
Section: Formulationsmentioning
confidence: 99%
“…big or small, spherical or not spherical, magnetically soft or hard, magnetic or non-magnetic, mechanically hard or soft, etc.). By using bidisperse MRFs one can improve dispersion stability, 95 reduce the off-state viscosity, 96 increase the MR effect 95,[97][98][99][100][101] and minimize the sedimentation. 97,98 First papers in this field explored mixing particles of different sizes (bimodal MRFs) with at least one particle in the micrometer range.…”
Section: Formulationsmentioning
confidence: 99%
“…A significant increase in shear stress was also obtained when adding 1% of γ-Fe 2 O 3 (Leong et al, 2016). The magnetorheological effect can be enhanced by several times with the use of magnetite additives (Ashtiani and Hashemabadi, 2015). A multiple increase in the components of the complex shear modulus and shear stress was also noted with the addition of non-magnetic particles of poly(methylmethacrylate) (Iglesias et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…Iron oxide has also been used in MRFs with other organic and inorganic additives. Korobko et al [ 101 ] reported shear stress of MRFs with CrO 2 additives to be greater than MRFs with γ‐Fe 2 O 3 or nonmagnetic SiO 2 in mineral oil, which the authors attribute to the higher M s and elongated structures of CrO 2 compared with γ‐Fe 2 O 3 and SiO 2 Ashtiani and Hashemabadi [ 102 ] found that MRFs with nonmagnetizable fumed silica exhibited higher off‐state viscosity, lower τ y values, and improved sedimentation stability as compared with MRFs with γ‐Fe 2 O 3 . Fu et al [ 103 ] observed that bidisperse MRF with a mixture of 15 wt% of gelatin‐coated CI and 2–5 wt% Fe 3 O 4 dispersed in polyolefin synthetic oil increased the sedimentation ratios of MRFs with increasing Fe 3 O 4 concentration.…”
Section: With Additives‐based Mrfsmentioning
confidence: 99%